Kelayakan Peningkatan Tarif Retribusi di Daya Tarik Wisata Taman Sari Water Castle Kota Yogyakarta: Kajian Kelayakan Biaya - Desy Rusmaningati; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
Tamansari Water Castle is a sub-tourist attraction located in the Keraton Yogyakarta complex, this tourist attraction is famous for its heritage buildings and also for its water palace. Since it was opened to tourists on April 1, 1974 many tourists visited this tourist attraction, both domestic and foreign tourists. Since the opening of this tourist attraction for the first time, which has not yet drawn retribution rates to tourists, there have been several times the rate of retribution increases to enter this tourist attraction. So there needs to be research on the feasibility of increasing the levy rate. In this regard, the author tries to examine the